2021
DOI: 10.20396/bjos.v20i00.8660445
|View full text |Cite
|
Sign up to set email alerts
|

Durability of bond strength to dentin using two universal adhesives in different etching modes

Abstract: Aim. To evaluate the bond durability of two universal adhesives; mild and ultra-mild in both etch-and-rinse and self-etch modes after simulated in-vitro degradation by long-term water storage or thermocycling. Methods. A total of 144 specimens were used in this study; 120 specimens (prepared from 30 teeth) for microshear bond strength testing and fracture mode assessment, and 24 specimens for scanning electron microscopic evaluation (prepared from 24 teeth). Specimens were prepared from 54 recently extracted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Universal adhesives were introduced essentially as selfetching adhesives, which by the operator's preference can be also used in the etch-and-rinse mode 5 . It was reported that light-and dual-cured universal adhesives showed similar bond strength when, they used in etch-and-rinse and self-etching modes 6,7 . However, the cumulative retention rate after 24-month of clinical evaluation showed that universal adhesives in the etch-and-rinse mode was significantly higher in their retention rate compared to the same adhesives when, used in the self-etching mode 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Universal adhesives were introduced essentially as selfetching adhesives, which by the operator's preference can be also used in the etch-and-rinse mode 5 . It was reported that light-and dual-cured universal adhesives showed similar bond strength when, they used in etch-and-rinse and self-etching modes 6,7 . However, the cumulative retention rate after 24-month of clinical evaluation showed that universal adhesives in the etch-and-rinse mode was significantly higher in their retention rate compared to the same adhesives when, used in the self-etching mode 8 .…”
Section: Introductionmentioning
confidence: 99%
“…81 Studies report that universal adhesives are material-dependent 4,14,111,112 and that long-term studies are still required to evaluate the stability of resindentin interfaces created by contemporary universal adhesives. 111,113,114 The clinical performance of universal adhesives largely depends on the adhesive strategy, thus questioning their claimed versatility regarding the application mode in a clinical setting. Several systematic reviews investigated which universal adhesive application mode (SE vs ER) was best for dentin and enamel adhesion.…”
mentioning
confidence: 99%